Body composition assessment: theory into practice: introduction of multicompartment models. - Siervo, M; Jebb, SA (2010)
The science of body composition is based on a series of models characterized by progressive levels of anatomical complexity: atomic, molecular, cellular, functional tissue, and whole body. The physiological characterization of the different components included in each model is based on a range of specific methods that exploit basic notions of physiology, statistics, and physics. The theoretical principles need to be fully understood to explain the potential of each method in research and clinical practice.